Development of the First Fluorescence Screening Assay for the SLC39A2 Zinc Transporter. (July 2014) - Franz, Marie-Christine; Simonin, Alexandre; Graeter, Stefanie; Hediger, Matthias A.; Kovacs, Gergely
Zinc is an essential micronutrient that is crucial for many vital cellular functions such as DNA and protein synthesis, metabolism, and intracellular signaling. Therefore, the intracellular zinc concentration is tightly regulated by zinc transporters and zinc-binding proteins. The members of the SCL39 transporter family transport zinc into the cytosol. The SLC39A2 (hZIP2) protein is highly expressed in prostate epithelial cells and was found to be involved in prostate cancer development. Thus far, there is no specific modulator available for the SLC39 transporters. The aim of this study was to develop a screening assay for compound screening targeting hZIP2. Employing the pIRES2-DsRed Express 2 bicistronic vector, we detected human ZIP2 expression at the plasma membrane in transiently transfected HEK293 cells. Using the FLIPR Tetra fluorescence plate reader, we demonstrated that ZIP2 transports Cd 2+ with an apparent Km value of 53.96 nM at an extracellular pH of 6.5. The cadmium influx via hZIP2 was inhibited by zinc in a competitive manner. We found that hZIP2 activity can be measured using cadmium in the range of 0.1 to 10 µM with our assay. In summary, for the first time we developed an assay for human ZIP2 that can be adapted to other zinc transporters.